2008
DOI: 10.1590/s0100-69162008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de redução do consumo de energia elétrica pela utilização de aquecedores solares no Estado de Goiás

Abstract: RESUMO:O presente trabalho analisa a viabilidade técnica da redução do uso de energia elétrica pela substituição dos chuveiros elétricos por aquecedores solares e apresenta uma análise da redução do custo mensal de energia elétrica para os diferentes municípios de Goiás. Por meio do processamento de dados climatológicos e com o auxílio do aplicativo de informações geográficas SPRING ® , foram calculados os valores de irradiâncias (MJ m -2 anual -1 ) e do número de horas anuais de brilho solar sobre a superfíci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 1 publication
1
8
0
6
Order By: Relevance
“…Studies have confirmed the technical and economic viability of domestic solar water heaters in many countries (Chandrasekar and Kandpal, 2004;Crawford and Treloar, 2004;Oliveira et al, 2008;Kalogirou, 2009;Gillingham, 2009;Naspolini and Ruther, 2012;Hang et al 2012;Cassard et al, 2011;Martinopoulos and Tsalikis, 2014;Ma et al, 2014). Besides, researches have also indicated that such water heaters have the potential to reduce greenhouse gas emissions from dwellings (Mirasgedis et al, 1996;Tsilingiridis et al, 2004;Kalogirou, 2009;Tsilingiridis and Martinopoulos, 2010;Shimoda et al, 2010;Hang et al, 2012;Sanders and Webber, 2015;Abd-Ur-Rehmana and Al-Sulaimana, 2016).…”
Section: Introductionmentioning
confidence: 87%
“…Studies have confirmed the technical and economic viability of domestic solar water heaters in many countries (Chandrasekar and Kandpal, 2004;Crawford and Treloar, 2004;Oliveira et al, 2008;Kalogirou, 2009;Gillingham, 2009;Naspolini and Ruther, 2012;Hang et al 2012;Cassard et al, 2011;Martinopoulos and Tsalikis, 2014;Ma et al, 2014). Besides, researches have also indicated that such water heaters have the potential to reduce greenhouse gas emissions from dwellings (Mirasgedis et al, 1996;Tsilingiridis et al, 2004;Kalogirou, 2009;Tsilingiridis and Martinopoulos, 2010;Shimoda et al, 2010;Hang et al, 2012;Sanders and Webber, 2015;Abd-Ur-Rehmana and Al-Sulaimana, 2016).…”
Section: Introductionmentioning
confidence: 87%
“…Home electricity consumption in Brazil corresponded to approximately 24% of total energy consumption in 2013 (Oliveira, Ferreira, Almeida, Lobato, & Medeiros, 2008), whereas the electric shower has a major slice in total energy consumption of households in Brazil, consuming approximately 26% of household electricity and totaling 6% of national consumption (Oliveira et al, 2008). Most electricity for heating is consumed during peak hours, from 18 to 21h (Basso, Souza, Siqueira, Nogueira, & Santos, 2010), the time of day characterized by end of business, activation of street lights, intensive use of household appliances, all imposing enormous pressure on the national interconnected system.…”
Section: Introductionmentioning
confidence: 99%
“…The collector may be used in various locations such as residential units, shopping malls, needy family's homes and on farms, where they may be used in heating water for cleaning milking equipment (Altoé & Oliveira Filho, 2010). The need of electricity for heating water decreases, especially in the case of showers, and electricity costs lowered (Oliveira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Além da questão ecológica, de acordo com OLIVEIRA et al (2008), a energia solar traz benefícios econômicos, tendo em vista o considerável consumo residencial de energia elétrica para aquecimento de água (NASPOLINI et al, 2010;KALOGIROU, 2009). MARTINS & PEREIRA (2011) citam também os benefícios sociais para as populações mais remotas, onde o custo da eletrificação pela rede conve ncional é proibitivo, caso de inúmeras propriedades rurais.…”
Section: Introductionunclassified